"Eu meio que fui costurando essa história": a trajetória de mulheres durante a ditadura civil-militar (1964-1985). - Faustino, Sinara Veiga (2021)
This research starts from the questioning of how women who were not part of organized political movements, and who had kinship links with imprisoned militants, experienced the dictatorial period in Brazil. They are women, mothers and daughters, who were also victims of repression and, like their fathers and husbands, suffered trauma from the military dictatorship that they keep until today. For writing, we analyzed six interviews, two of them with activists' wives and four with daughters. The time frame works with prisons from 1964 to 1984, covering persecutions that started at the beginning of the coup, up to arrests carried out close to 1984. All interviewees live and experienced the dictatorship in the state of Rio Grande do Sul, justifying our spatial approach. The testimonies of these women allow us to analyze how the repression affected different people, not only those arrested and persecuted, but also their families, permeating gender relations, and discussing the traumas that were often ignored and silenced. In this sense, our research seeks to highlight the trajectory of women who, even though they are not linked to an organized resistance, also had to resist and bear the ailments of family militancy, experiencing traumatic situations and, in many cases, not having a space for listening.